Photo-induced electron trapping in indirect bandgap AlxGa1-xAs : Si at low temperature - Scalvi, LVA; Taquecita, M. H.; Vega, BAV (Iop Publishing Ltd, 1999)
A variation of photoconductivity excitation with wavelength is applied to Si-doped Al0.56Ga0.44As (indirect bandgap material) for a wide range of temperature. The lower the temperature the lower the photocurrent below 70 K. In the range 13-30 K there is a decrease in the photoconductivity spectrum slightly above the bandgap transition energy, followed by another increase in the conductivity. We interpret these results in the light of existing models and confirm the trapping by the X-valley effective mass state. which is responsible for attenuation of persistent photoconductivity below 70 K. A DX0 intermediate state which has non-negligible lifetime is proposed as responsible for the decrease in the photoconductivity with about 561 nm of wavelength of exciting light, in the investigated 13-30 g range.